Color in interior design - Pile, John F. (New York : McGraw-Hill, 1997)
Introduction. Color in interior design. Vision, light, and color. Color systems. The color wheel. Color charts. Color schemes. Color schemes in practice. From charts to realization. Analysis of color schemes...
Keywords: Color; Color in interior decoration